Study of the degradation of the antibiotic Sulfamethoxazole and Trimethoprim(ST) from light-mediated CuO and ZnO nanoparticles - Madeira, Gustavo Henrique de Lima (Seven Editora, 2023)
The discovery of natural antibiotics was considered a revolution for medicine at the time, capable of easily curing bacterial diseases that had no cure. However, the inappropriate use and disposal of these drugs ended up causing an accelerated development of bacteria, causing a natural selection of strains capable of resisting these antibiotics. To try to avoid this evolution, it is necessary to degrade these drugs before disposal. One way to cause this degradation is to apply ultraviolet radiation on the molecular structure of the antibiotic, providing energy for the breakdown and degradation of the structure, in a photocatalysis process. The application of certain nanoparticles can accelerate the degradation process, such as copper oxide (CuO) and zinc oxide (ZnO), which are used as photocatalysts, as they absorb at low energy (visible light) and at higher energy ( UV), and also for being able to recover them after use. The results of the UV-Vis absorption spectroscopy show that the use of nanoparticles was responsible for accelerating the antibiotic degradation process by 1.68x when compared to the use of only UV radiation. DOI:https://doi.org/10.56238/sevened2023.006-048